Função afim aplicada na produção e comercialização da palmeira Euterpe oleracea - COUTO, Rosenildo Couto do (2022)
The açaí as a fruit of the açaizeiro has been one of the main economy of Pará due to the significant commercialization of the regional, national and international market. In view of this approach, the present course conclusion work proposes as a theme a related function applied in the production and commercialization of the euterpe oleracea palm (açaizeiro). In this sense, the affine is used to understand its applicability in problems associated with the commercialization of the fruit considering a field research in the lower community of Itacuruçá located on the island belonging to the city of Abaetetuba. For a better understanding of the work, an exploratory research of a producer living in the community is used to verify the financial balance that he acquires during the harvest and off-season periods, evaluating the additional expenses and trips of the fruit from the community to the urban area where the sale takes place. . A qualitative and quantitative questionnaire is directed to the product to ascertain the territorial space where the planting of palm trees takes place. The research is concluded considering that the PR producer (name used for not identifying the interviewee) has a greater profit during the harvest period because he has a plantation of 5000 palm trees, which ensures him a number of 15,000 shallow during the period of harvest and in the inter-harvest period, in which the management period decreases, it reaches a value of 7,500 shallows.